XVModern Literature. (29th October 2018) - Levay, Matthew; Radford, Andrew; Krzakowski, Caroline; Keese, Andrew; Dick, Maria-daniella; Livingstone, Catriona; Tweed, Hannah; MartÍn, Gustavo A RodrÍGuez; Saunders, Graham; Baker, William; Creasy, Matthew; O'Hanlon, Karl; et al.
Abstract: This chapter has 8 sections: 1. General; 2 Pre-1945 Fiction; 3. Post-1945 Fiction; 4. Pre-1950 Drama; 5. Post-1950 Drama; 6. British Poetry 1900–1950; 7 British Poetry Post-1950; 8. Irish Poetry. Section 1 is by Matthew Levay; section 2(a) is by Andrew Radford; section 2(b) is by Caroline Krzakowski; section 2(c) is by Maria-Daniella Dick; section 2(d) is by Andrew Keese; section 2(e) is by Catriona Livingstone; section 3(a) is by Hannah Tweed; section 3(b) is by Samuel Cooper and William Baker; section 4 is by Gustavo A. Rodríguez Martín; section 5 is by Graham Saunders and William Baker; section 6 is by Matthew Creasy; section 7 is by Karl O'Hanlon; section 8 is by Adam Hanna.